2021
DOI: 10.3390/v13101889
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evolution of West Nile Virus at Higher Temperatures Facilitates Broad Adaptation and Increased Genetic Diversity

Abstract: West Nile virus (WNV, Flaviviridae, Flavivirus) is a mosquito-borne flavivirus introduced to North America in 1999. Since 1999, the Earth’s average temperature has increased by 0.6 °C. Mosquitoes are ectothermic organisms, reliant on environmental heat sources. Temperature impacts vector–virus interactions which directly influence arbovirus transmission. RNA viral replication is highly error-prone and increasing temperature could further increase replication rates, mutation frequencies, and evolutionary rates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…In Europe 315 human cases of WNV infection were observed during the 2020 transmission season, but some countries reporting low numbers of infections had detected higher numbers of human WNV infections (e.g., Austria, Hungary, Serbia, Romania) in previous years, probably due to the herd immunization enhanced by highlevel circulation in earlier periods. It is notable that the high temperature favors the selection of mutant strains that can evade host immune response and support WNV outbreak in previously apparently protected areas [45,46].…”
Section: N Discussionmentioning
confidence: 99%
“…In Europe 315 human cases of WNV infection were observed during the 2020 transmission season, but some countries reporting low numbers of infections had detected higher numbers of human WNV infections (e.g., Austria, Hungary, Serbia, Romania) in previous years, probably due to the herd immunization enhanced by highlevel circulation in earlier periods. It is notable that the high temperature favors the selection of mutant strains that can evade host immune response and support WNV outbreak in previously apparently protected areas [45,46].…”
Section: N Discussionmentioning
confidence: 99%
“…This rests on the assumption of no evolution. However, temperature‐dependent evolution of the WNV has been shown in the lab (Fay et al., 2021 ) and in the field (Bialosuknia et al., 2022 ). A further caveat is this research was purely from the standpoint of WNV.…”
Section: Discussionmentioning
confidence: 99%
“…tarsalis in the US and other Culex species implicated in enhanced WNV transmission in Europe [ 23 , 58 , 59 ]. Additionally, changes to the environment, particularly increases in temperature associated with climate change, may facilitate broad adaptation, perhaps expanding the host and geographical range of the virus [ 60 ]. Importantly, while our previous studies only identified the NY10 genotype in NYS, it is now present throughout the continental US, suggesting that it may have a broad adaptive advantage that could drive similar increases in WNV activity in other regions (nextstrain.org/wnv/na).…”
Section: Discussionmentioning
confidence: 99%